"All shook up" : the archival legacy of Terry Cook - Nesmith, Tom; Bak, Greg, 1969-; Schwartz, Joan M., 1951- (Society of American Archivists ; Association of Canadian Archivists, 2020)
"Thirteen of Cook's groundbreaking articles are brought together in a single volume. They're paired with commentaries by leading archival thinkers from several countries who reflect on his influence as a scholar, colleague, educator, and mentor. The articles span his career, starting with an initial foray into archival literature in 1979 and ending in 2013, a year before his death. The range is prodigious: the history/archives debate, archival appraisal, the post-custodial era, digital records, Indigenous peoples and justice with archives, the records continuum, postmodernism, and power, memory, and identity"--cover
With a comprehensive bibliography of the writings of Terry Cook by Jennifer Rutkair, p. 485-498. Includes index, p. 506-522.
Keywords: Cook, Terry, -- 1947-2014.; Archives -- Administration; Archival resources